ANALYSIS OF NURSING CARE IN POST-CRANIOTOMY TRAUMATIC BRAIN INJURY PATIENTS WITH HYPERTHERMIA USING WARM COMPRESS INTERVENTION - Ilhamsyah (Jurnal Kesehatan, 2022)
The World Health Organization indicates that 16,500 people worldwide die every day from all kinds of injuries. One of them is a head injury whose cases are often found in the hospital's treatment room or the intensive care unit. Factors that aggravate the condition of post-craniotomy head trauma patients during hospitalization in the ICU, such as decreased consciousness, cerebral edema, pupillary dilatation, increased intracranial pressure, seizures, and fever/increased body temperature. Fever in head trauma patients can be caused by inflammation, infection, or damage to the hypothalamus, causing an increase in metabolic rate and increased intracranial pressure, which can cause additional trauma such as seizures, dehydration, and even shock. Warm the patient with a cloth and warm water. Objective: Analysis of health care in post-craniotomy brain trauma patients with hyperthermia using warm compress intervention in the ICU. Method: A case study with data collection techniques through interviews, observation, physical examination, and documentation. Warm compresses are applied when the patient is hyperthermic and stops when the body temperature drops. Results: Data analysis showed that warm compress intervention was effective in reducing body temperature in post-craniotomy traumatic brain injury patients with hyperthermia. Conclusion: it was concluded that warm compresses effectively deal with hyperthermia problems.